How does HPV vaccination status relate to risk perceptions and intention to participate in cervical screening? a survey study - Mie Sara Hestbech; Dorte Gyrd-Hansen; Jakob Kragstrup; Volkert Siersma; John Brodersen (BMC, 2016)
Abstract Background Women in several countries will soon be covered by two preventive programmes targeting cervical cancer: HPV vaccination and cervical screening. The HPV vaccines are expected to prevent approximately 70 % of cervical cancers. It has been speculated, that HPV vaccinated women will not attend screening because they falsely think that the vaccine has eliminated their cervical cancer risk. The aim of this study was to investigate the association between HPV vaccination status and perceptions of cervical cancer risk; perceptions of vaccine effect; and intention to participate in cervical screening. Furthermore, to investigate associations between perceptions of cervical cancer risk and intention to participate in cervical screening. Methods A random sample of Danish women from the birth cohorts 1993-1995 was invited to complete a web-based questionnaire concerning risk perceptions and intentions to participate in cervical screening. Main outcomes were: perceived lifetime-risk of cervical cancer; perceived HPV vaccine effect; and intention to participate in cervical screening. Results HPV vaccinated women more often than unvaccinated women intended to participate in screening: adjusted odds ratio (OR) for being HPV vaccinated when intending to participate in screening of 3.89 (95 % CI: 2.50-6.06). HPV vaccinated women perceived cervical cancer risk to be higher than unvaccinated women did: adjusted OR of 0.11 (95 % CI: 0.03-0.39) and 0.51 (95 % CI: 0.33-0.78) for being HPV vaccinated while having the lowest perception of risk (in two different pre-specified dichotomisations). HPV vaccinated women perceived the vaccine effect to be larger than unvaccinated women did: adjusted OR of 0.31 (95 % CI: 0.18-0.51) and 0.37 (95 % CI: 0.25-0.53) for being HPV vaccinated while having the lowest perception of vaccine effect (in two different pre-specified dichotomisations). There were no associations between perceived cervical cancer risk and intention to participate in screening. Conclusions HPV vaccinated women more often than unvaccinated women intended to participate in screening and they perceived cervical cancer risk to be higher and the vaccine effect to be larger than unvaccinated women did. However, in our analyses, risk perceptions could not explain screening intentions neither among vaccinated nor among unvaccinated women.